2020
DOI: 10.1186/s12302-020-00310-z
|View full text |Cite
|
Sign up to set email alerts
|

Benefits from hazards, benefits from nothing, and benefits from benefits: the combined effects of five quaternary ammonium compounds to Vibrio qinghaiensis Q67

Abstract: Background Co-exposure of multiple quaternary ammonium compounds (QACs) is widely present in the aquatic environment. The knowledge about their toxicities to microorganism at low concentration is lacking. This study aims to test the toxic response of Vibrio qinghaiensis Q67 (12-h exposure) to individual and mixtures of QACs by the long-term microplate toxicity analysis method (L-MTA). Results Hormetic effects were observed for five individual QACs at 12-h exposure of Vibrio qinghaiensis Q67. The maximum stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…These chemicals are used for both hand and surface sanitizer products and are among the most widely applied disinfectants during the current pandemic (Dhama et al, 2021;Jing et al, 2020; World Health Organization (WHO), 2020). Importantly, hormesis was induced by not only single chemicals but also mixtures, specifically in studies with QACs, which can display also additive or synergistic effects (Mo et al, 2020); hormetic effects of complex mixtures of chemicals have also been reported by numerous other studies (Docea et al, 2019;Tsatsakis et al, 2019). Extensive experimentation with yeast subjected to a series of dilutions of numerous disinfectants revealed that most of the disinfectants induced toxicity followed by an overcompensation stimulation (Branham, 1929).…”
Section: Presentation Of the Analysis And Concernsmentioning
confidence: 94%
See 1 more Smart Citation
“…These chemicals are used for both hand and surface sanitizer products and are among the most widely applied disinfectants during the current pandemic (Dhama et al, 2021;Jing et al, 2020; World Health Organization (WHO), 2020). Importantly, hormesis was induced by not only single chemicals but also mixtures, specifically in studies with QACs, which can display also additive or synergistic effects (Mo et al, 2020); hormetic effects of complex mixtures of chemicals have also been reported by numerous other studies (Docea et al, 2019;Tsatsakis et al, 2019). Extensive experimentation with yeast subjected to a series of dilutions of numerous disinfectants revealed that most of the disinfectants induced toxicity followed by an overcompensation stimulation (Branham, 1929).…”
Section: Presentation Of the Analysis And Concernsmentioning
confidence: 94%
“…1). Examples of such chemicals shown to induce hormesis include chlorine-based chemicals (Zhang et al, 2008), H 2 O 2 (Huang et al, 2019;Ludovico and Burhans, 2014;Semchyshyn, 2014;Semchyshyn and Valishkevych, 2016), various QACs (Hrubec et al, 2021;Li et al, 2019;Mo et al, 2020), and ethanol (Calabrese and Baldwin, 2003;Kar et al, 2021;Semchyshyn, 2014). These chemicals are used for both hand and surface sanitizer products and are among the most widely applied disinfectants during the current pandemic (Dhama et al, 2021;Jing et al, 2020; World Health Organization (WHO), 2020).…”
Section: Presentation Of the Analysis And Concernsmentioning
confidence: 99%
“…Similarly, the joint action of ATMAC C16 and fluoranthene (Flu) also shifted from a synergetic toxic effect to an antagonistic effect when the levels of Flu grew from 50 µg/L to 200 µg/L ( Yu et al, 2013 ). When the mixture of QACs is present in low concentrations in the environment, some hormetic effects are observed ( Agathokleous et al, 2022 , Mo et al, 2020 ). It may enhance the propagation of pathogenic microbes and increase the spread of antibiotic resistance.…”
Section: Toxicity Of Qacs To Aquatic Organisms and Humanmentioning
confidence: 99%
“…Hormesis describes a dose-effect relationship characterized by low-dose stimulation and high-dose inhibition. The hormetic effects of heavy metals [37], sulfonamides [38] and ionic liquids [39] on luminescent bacteria have been reported.…”
Section: Toxicological Significancementioning
confidence: 99%